SÍNDROME METABÓLICA EM AMBULATÓRIO DE CARDIOLOGIA EM SÃO LUÍS MARANHÃO - Barbosa, José Bonifácio (2008)
The metabolic syndrome (MS) is responsible for increasing cardiovascular morbidity and mortality in the entire world. However, it remains as a complex entity because it has no clear definition and also by the lack of uniformity in the diagnostic criteria. Thus, there are many controversies regarding its exact prevalence in non-selected populations and few studies performed in cardiology outpatient clinic, where the population presents multiple risk factors and the MS can be an aggravating finding determining changes in the therapeutical strategies. The purpose of this research were: to determine the prevalence of MS according to the criteria of the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATPIII) and the International Diabetes Federation (IDF), to evaluate the differences of the prevalence in both sex, to establish the correlation of MS and other risk factor and cardiovascular diseases (CVD), and to analyze the concordance between the two methods by Kappa. The prevalence was 54.4% and 63.6% according to the NCEP ATPIII and IDF respectively. Considering the gender, the prevalence was higher in female (59%) by the criteria of the NCEP ATPIII. Coronary artery disease (CAD) presented higher frequency among patients with MS (28.4% NCEP ATPIII and 24.3% IDF, p<0.001), but this correlation was not seen among those who had stroke. Age > 40 years and body mass índex (BMI) > 30kg/m² were the variables more frequently associated with a greater risk of MS (p<0,001) after the adjusted analysis of risk factors by the IDF criteria. The general concordance between the two criteria was 0.70 (p<0.001), which was higer in female, 0.82 than in male, 0.85. In conclusion, the prevalence of MS in cardiology outpatient clinic is higher than for the general population with predominance of female sex by the NCEP ATPIII and it has been associated with CAD. There was a good concordance of the two methods used to evaluate the MS; wich was great for the female sex and just regular for male, suggesting that criteria currently utilized for the diagnosis of MS are not adequate for the male sex. It is likely that the cut-off of the waist circunference utilized by the IDF has been responsible for the low concordance found in the female sex by the two definitions.